Clinical researchAge and gender as determinants of response to prolonged tilting in patients with syncope - Lelonek, Małgorzata; Goch, Jan H. (Archives of Medical Science, 2008)
Introduction: There are still many questions about factors and predictors of positive tilting. The main goal of the study was to identify an association between age and gender of syncopal patients and the outcome of head-up tilt testing (HUTT). Material and methods: 470 patients (men 41%, mean age 46.5±18.7 years) with recurrent syncope (more than 2 episodes in the last 3 months) were tilted and divided according to HUTT outcome: negative HUTT(–) and positive HUTT(+), and next according to type of Vasovagal Syncope International Study (VASIS): VASIS1 – mixed, VASIS2 – cardioinhibitory and VASIS3 – vasodepressor. Results: HUTT(+) was observed in 300 patients (64%), including 172 cases of VASIS1, 47 of VASIS2 and 81 of VASIS3. HUTT(+) did not depend on age or gender of patients. Older age and male gender were positively associated with VASIS3 response (OR 1.02, CI 1.00-1.04, p=0.015 and OR 2.01, CI 1.14-3.54, p=0.0015 respectively). Time to syncope during passive tilting positively correlated with age of patients (r=0.244, p=0.030) and depended on VASIS reaction (r=0.336, p=0.003). Conclusions: Positive result of tilting depends neither on age nor gender. Time to syncope onset during passive tilting is related to age and VASIS reaction. Older age and male gender are positively associated with VASIS3 response.